The association between moral distress and moral courage in nurses: A cross-sectional study in Iran - Hamid Safarpour; Mohammad Ghazanfarabadi; Saeideh Varasteh; Jafar Bazyar; Masoumeh Fuladvandi; Leila Malekyan (Wolters Kluwer Medknow Publications, 2020)
Background: Moral distress and moral courage among healthcare professionals have received considerable attention in recent years. However, there is a paucity of studies investigating these topics among nurses. Thus, the present study aimed to evaluate the association between moral distress and moral courage among nurses in an Iranian sample population. Materials and Methods: The present cross-sectional study was conducted during February-December 2018. Corley's Moral Distress (MDS-R) and Sekerka's moral courage scales were used to collect the data. MDS-R is a 21-items scale which includes frequency and intensity ranges from 0 (never) to 4 (very frequently) and 0 (none) to 4 (great extent), respectively. In addition, the moral courage scale contains 15 items ranging from "never true" (1 point) to "always true" (7 points). In total, 225 eligible nurses were entered into this study. Finally, SPSS-16 was used for statistical analysis at the α = 0.05 level. Results: The mean scores of the frequency and intensity of moral distress and moral courage were 45.41 (95% CI = 43.37-47.45), 44.24 (95% CI = 42.98-45.42), and 59.63 (95% CI = 58.50-60.87), respectively. Eventually, a significant relationship was found between the moral courage and frequency of moral distress (r = 0.46, p < 0.001) and the intensity of moral distress (r = 0.73, p < 0.001). Conclusions: In general, encouraging healthcare managers and administrators is considered as crucial for developing supportive structures and highly sensitive management which promotes moral courage while reducing moral distress in nurses' work setting.